PECULIARITIES OF THE RESIDENTIAL REAL ESTATE MARKET AND THE INFLUENCE OF FINANCIAL AND CREDIT INSTRUMENTS ON ITS DEVELOPMENT IN UKRAINE - Shteingauz , Dmytro (Socio-economic relations in the digital society, 2021)
Abstract. The article examines the features of the functioning and the main trends in the development of the domestic residential real estate market at the present stage. The purpose of the study is to identify the main trends in the domestic residential reale state market at the present stage, to analyze the problems and to identify promising are as of financial and credit instruments to ensure the effective functioning of the residential reale state market in Ukraine. The dynamics of consumer demand by the number of transactions of purchase and sale of housing against the background of the COVID-crisis, the structure of demand by size and level of comfort of housing, the dynamics and structure of capital investment in housing by type of assets. Problems of inadequate financing of the needs of repair, reconstruction and renovation of the old housing stock have been identified, which in the long run will lead to deterioration in the quality of residential real estate sold on the secondary market. There is a need to revise the state financial policy in the field of housing construction and create new financial and credit instruments that will ensure the effective functioning of the residential real estate market. It is revealed the low level of investment opportunities of the population in the field of housing construction and the need to develop financial and credit tools to expand alternative opportunities for investment in the construction / purchase of housing. This paper outlines the ways of solving the socially significant problem of providing the population of Ukraine with affordable housing of proper quality. It is grounded that the main expected trends that will affect the distribution of financial flows and determine possible areas for improvement of financial and credit instruments in the residential real estate market of Ukraine, namely: 1) redistribution of capital between real estate classes and a sharp increase in investment in apartment buildings; 2) favorable opportunities for the development of the market of preferred shares and various derivative financial and credit instruments; 3) dissemination and improvement of digital tools as a component of ensuring the use of financial and credit tools; 4) maintaining the high risk of the real estate market for both investors and creditors, which necessitates improving the existing system of financial monitoring and financial control, as well as creating a system of insurance for residential real estate, as this market concentrates significant investments. Keywords: residential real estate market, housing construction, financial security, capital investments, financial and credit instruments, consumer demand, affordable housing. JEL Classification G21 Formulas: 0; fig.: 2; tabl.: 0; bibl.: 5.